Comparative Analysis Of Electronic Agreement Regulations Online Arisan In Indonesia And Malaysia : (Study Decision No. 106/Pdt.G/2017/Pn Plk) - Tanjung, Salsas Bila Juniyanti; Winanti, Atik (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2025)
The development of information technology has transformed the way people engage in economic activities, including the conduct of online arisan (rotating savings groups). Online arisan represents an electronic agreement between parties that does not require written documentation but still establishes legally binding rights and obligations. This study aims to analyze and compare the legal regulations governing online arisan agreements in Indonesia and Malaysia, using Decision No. 106/Pdt.G/2017/PN Palangka Raya as a case study. The research employs a normative legal method with statutory, case, and comparative approaches. The results show that in Indonesia, online arisan agreements are considered valid as long as they fulfill the requirements stipulated in Article 1320 of the Indonesian Civil Code and are carried out in accordance with the principles of freedom of contract, good faith, and pacta sunt servanda. Meanwhile, in Malaysia, online arisan activities, also known as kumpulan wang kutu, are regulated under several laws, including the Contracts Act 1950, the Electronic Commerce Act 2006, and the Kumpulan Wang Kutu (Prohibition) Act 1971. This study concludes that Indonesia emphasizes contractual freedom and legal validity, while Malaysia prioritizes consumer protection through strict prohibition, reflecting fundamentally different regulatory approaches to online collective financial arrangements.